Video-EEG monitoring as a valuable tool for antiseizure medication withdrawal in patients with epilepsy: implications for clinical practice and public health policies - Obed Okwoli Apochi (Neurological Research and Practice, 2023)
Abstract This letter to the editor discusses “the use of video-EEG monitoring to guide antiseizure medication (ASM) withdrawal in patients with epilepsy” [1]. The author highlights the potential benefits of this approach, including reduced risk of seizure recurrence and improved patient outcomes. The author also notes the need for further research to refine the criteria for identifying patients who are good candidates for ASM withdrawal and to evaluate the effectiveness of this approach in different patient populations and settings. Finally, the author discusses the implications of these findings for public health policies related to epilepsy management.